2021
DOI: 10.1002/etc.5202
|View full text |Cite
|
Sign up to set email alerts
|

Are Fragrance Encapsulates Taken Up by Aquatic and Terrestrial Invertebrate Species?

Abstract: The uptake potential of Fragrance Encapsulates (FEs) by aquatic or terrestrial organisms was investigated. Due to their size of below 5 mm and their This article is protected by copyright. All rights reserved. Accepted Articlepolymeric nature, FEs fall under the Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection (GESAMP) definition of microplastics (MPs).After use, FEs enter the sewer system and reach the sewage treatment plant (STP) where >90% of the FEs are likely to be remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Furthermore, exposure via the soil poses another challenge because it significantly complicates the analysis. For instance, the advantage of using fluorescent material which cannot be accurately measured in soil matrix is lost (see Kuehr et al, 2022). Alternatively, much more complex and expensive analytical methods, such as the use of radiolabeled particles, would need to be applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, exposure via the soil poses another challenge because it significantly complicates the analysis. For instance, the advantage of using fluorescent material which cannot be accurately measured in soil matrix is lost (see Kuehr et al, 2022). Alternatively, much more complex and expensive analytical methods, such as the use of radiolabeled particles, would need to be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Again, nano‐polystyrene (47 nm) and micro‐polystyrene (100 nm) were used as test particles. Animals were exposed as described by Kuehr et al (2022) with minor modifications. In brief, per test setup, 300 amphipods were exposed in 5 L tap water in a 15‐L glass aquarium with daily water exchange.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the group of micro‐ and nanoplastics, fragrance encapsulates are a specific group consisting of thermoset polymers which differ in properties from the thermoplast polymers often found in the environment (de Haan et al, 2019). Kuehr et al (2022) found limited species‐specific effects of fragrance encapsulates on aquatic and terrestrial invertebrates. In terms of exposure assessment and risk assessment, Cai et al (2022) derived both predicted‐environmental concentration and predicted‐no‐effect concentration values and suggest no environmental risk based on the present data.…”
mentioning
confidence: 99%